PERENCANAAN PEMELIHARAAN MESIN PRODUKSI DENGAN MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) (Studi Kasus: PT. S) - Prasetya, Dwi; Ardhyani, Ika Widya (JISO : Journal of Industrial and Systems Optimization, 2018)
PT. S is a company that produces steel pipe. As a manufacturing company, the company relies heavily on its production machines, one of the main engines in this company is  mill 303. However, the high frequency of failure and downtime caused the production decreased. This research use reliability centered maintenance (RCM) method. This method is used to determine the machine maintenance schedule as well and the interval optimal time. The stages of this research begin with determining the critical machine then make the system description followed by FMEA analysis, ABC analysis to determine critical component, FTA analysis, analysis of time distribution up to interval optimum maintenance. The result of this research is known 11 critical component with highest RPN value. 11 components that have been identified then analyzed the distribution of the time to failure and distribution of the time to repair and get the value of MTTR and MTTF. Bearing drive roll is the component with the highest RPN value of 512, the MTTR value of 3.56259, the MTTF value of 730,537 and the optimal maintenance interval of 504.64 hours.